Why motivating people doesn't work ... and what does the new science of leading, energizing, and engaging - Fowler, Susan 1951- (San Francisco, California Berrett-Koehler Publishers, 2014)
"Based on the latest research and extensive work with hundreds of companies, Susan Fowler has a shocking message to leaders about motivating their people: STOP! In this groundbreaking book, Susan shows leaders how they can get out of the way and encourage their people to learn the skills of self-motivation"--Publisher.
Includes bibliographical references and index.
Keywords: Employee motivation; Leadership